Membumikan SDGs: Pemberdayaan Komunitas untuk Perilaku Hidup Sehat dan Sejahtera di Dusun Kendal - Novriest Umbu Walangara Nau; Rully Adi Nugroho; Desti Christian Cahyaningrum; Debora Natalia Sudjito; Desi Desi; Michael Bezaleel Wenas (PELITA NUSA TENGGARA, 2026)
The Sustainable Development Goals (SDGs) provide a global development framework that is human-centered and inclusive. SDG 3—Good Health and Well-Being—targets the prevention of endemic diseases caused by waste accumulation (Target 3.3) and the reduction of mortality and illness resulting from pollution and contamination of air, water, and soil (Target 3.9). Kendal Hamlet, Samirono Village, Getasan District, Semarang Regency, faces challenges in realizing healthy and prosperous community living, particularly due to low public awareness of clean and healthy lifestyle behaviors and limited household waste management capacity. To localize and “ground” SDGs at the grassroots level, the community service team implemented a 3-day Live In program using a participatory approach. Students lived with local host families, acting as foster families, to conduct joint observation, discussion, and collaborative, two-way solution implementation, aligned with Whole Person Education principles and the SDGs commitment to no one left behind. The program improved environmental health literacy, promoted safer pesticide application through the use of personal protective equipment, and introduced housefly mitigation strategies based on sanitation and local wisdom. The activities ran successfully and received highly positive responses from residents and hamlet authorities, demonstrating that immersive community engagement strengthens local capacity and encourages sustainable, collective action in support of SDG 3 achievement.